L’anaphore en THE, mode d’accommodation dans la presse généraliste et d’intérêt spécialisé des États-Unis. - Caroline Peynaud (Anglophonia)
Journalists produce a discourse that is highly constrained by the norms of the genre and by the need to produce an attractive discourse which is adapted to readers. This will to adapt is part of an accommodation process by which the authors adapt their discourse to their readers, without knowing them very precisely, while the readers, in turn, interpret the discourse according to their knowledge of the norms of the genre. The analysis of accommodation modes makes it possible to understand more precisely the relationship journalists build with their readers. The case of loose and associative THE-anaphora is especially revealing of the choices journalists make to present information as old or new, to the extent that the choice to present information in a definite form cannot systematically be justified by shared knowledge. These choices thus illustrate an accommodation process by which journalists present information as old although it is likely to be new for readers. These analyses are based on a 35 000-word press corpus. They evidence the fact that these choices allow journalists to obey genre-specific constraints. When the referent is the main topic of an article, anaphors build designation paradigms that enhance cohesion. Conversely, when the referent is a secondary topic, anaphors make it possible to background information, while providing all the elements that may be necessary to understand the article.